Social thought and political positioning: social representations of the right and the left in Colombia - Echeverri Vásquez, Georgie; Santana Peixoto, Álvaro Rafael; Rosas Torres, Ana Raquel (Pensando Psicología, 2021)
Introduction: Social representations are common sense theories about a controversial object, which are constructed consensually by groups. From the point of view of interactional epistemology, social representations are forms of social thought or schemes for interpreting the world directly associated to social practices, that is, to the way groups behave. Objectives: 1) To identify the possible social representation of the ‘right’ and the ‘left’ in Colombia. 2) To establish the relationship between the mobilizing effect of the label and the adherence or rejection of postulates of both ideological strands. Method: A questionnaire was applied to 104 Colombian adults, segmented according to their ideological orientation of right, left or center. The questionnaire contained a word-free association technique, from which a prototypical analysis and a similarity analysis were performed; and a Likert scale, based on which an ANOVA test was carried out. Results: A possible social representation of the ‘right’ structured around former president Álvaro Uribe and two possible representations of the ‘left’ were identified, one linked to communism and the other to expectations for the consolidation of the peace process. Based on the theory of social identity, it was also possible to show in left voters the mobilizing effect of the label as a trigger of a social representation linked to group identity.